Grounding Islamic Messages in Nature Protection: Tiktok untuk Dakwah Virtual Dengan Menggunakan Metode Maw'izhah Al-Hasanah - Jauza, Alfiyah Zahra; Sucipto, Ade; Sutari, Bunga Maretianti; Parhan, Muhamad (Peneliti.net, 2025)
This research examines the use of TikTok as a virtual da'wah medium in the context of nature protection using the Maw'izhah Al-Hasanah method. In the digital era, social media such as TikTok offers a broad platform for spreading religious messages, including messages about the importance of protecting the environment. The Maw'izhah Al-Hasanah method, which emphasizes a persuasive approach and good delivery, is very relevant to be applied in da'wah campaigns on social media. This literature study explores various sources that discuss the use of TikTok as a da'wah tool, the effectiveness of the Maw'izhah Al-Hasanah method in virtual communication, and the relevance of Islamic messages regarding nature protection in the modern context. The results of this study show that TikTok has great potential as a propaganda medium, with the Maw'izhah Al-Hasanah method being able to have a positive impact in conveying messages about nature protection that are in accordance with Islamic teachings. In addition, this research highlights the challenges and opportunities in integrating digital technology with traditional methods of da'wah, as well as the importance of adapting religious messages in formats that are attractive and easy to understand by the millennial generation.